Is It Necessary to Prepare the Enamel before Dental Bleaching? - Andréa Dias Neves Lago; Patrícia Moreira de Freitas; Erika Michele dos Santos Araújo; Adriana Bona Matos; Narciso Garone-Netto (Hindawi Limited, 2017)
The aim of this in vitro study was to assess the influence of distinct surface treatments on the microhardness and color of enamel that will be bleached. Surface treatments are tested, accordingly: G1, no treatment; G2, 2% sodium fluoride; G3, casein phosphopeptide paste; G4, 2% fluoride+Nd:YAG laser. Forty blocks from bovine teeth composed the sample that were tested in Knoop microhardness (n=10) and in color change (n=10). After 24 h, bleaching with 35% hydrogen peroxide was performed for 45 min. Microhardness and color changes (using parameters ΔE, ΔL, Δa, and Δb) were assessed before and after bleaching. The data were analyzed by two-way ANOVA and Tukey's test (p<0.05). Despite all surface treatments, a reduction of enamel microhardness occurred immediately after bleaching in all groups, being greater in G1. Enamel color changed in all groups. Immediately after bleaching, there was a decrease on enamel microhardness. However, after 7 days, some of those specimens previously treated before bleaching significantly recovered their initial microhardness without influencing the esthetic results of bleaching.